Bogor Go Digital Strategy The KKN Strategy Behind the Empowerment of Waru Village - Awaldi Agung; Muhammad Daffa Albari; Sahrul Ramadhan; Ilham Firdaus; Muhammad Ihsanul Azim; Muhammad Raihan Nafi; Arto Widodo; Agung M.Natsir; Larasati; Muhammad Abdi Rahman; Widodo (Society : Jurnal Pengabdian Masyarakat, 2026)
TThe Community Service Program (KKN) conducted by Group 3 ITB Ahmad Dahlan in Waru Village, Parung District, Bogor Regency, West Java aims to address several issues faced by the local community. The main issues identified include the lack of public knowledge regarding digital branding for Micro, Small, and Medium Enterprises (MSMEs), the unavailability of clear directional signs towards village facilities, and the low awareness of the importance of environmental cleanliness. To achieve these objectives, this program was designed with several intervention methods. The results of this KKN activity show an increase in community understanding of digital branding, the creation of creativity in arts, as well as the installation of 9 sign systems that were successfully carried out in Waru Village. This activity not only provides direct benefits to the community but also offers valuable experience for students in applying the knowledge they have learned in college. It is hoped that this initiative can continue and create a lasting positive impact for the community of Waru Village